2018
DOI: 10.14260/jemds/2018/483
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Fentanyl, Butorphanol and Nalbuphine in Attenuation of Haemodynamic Responses in Laparoscopic Cholecystectomy

Abstract: BACKGROUND Numerous attempts have been made in the past to attenuate the haemodynamic responses occurring during laparoscopic cholecystectomy. The present study compared the effect of three opioids namely Butorphanol, Fentanyl and Nalbuphine in obtundation of haemodynamic responses in laparoscopic cholecystectomy in terms of Heart rate, BP (SBP, DBP and MAP) and secondary aim was to calculate duration of analgesia and sedation score. MATERIALS AND METHODS This was a randomised study comparing three opioid drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(3 reference statements)
1
4
0
Order By: Relevance
“…[14][15][16] In study by Rekhi et al they found nalbuphine (0.2mg/kg) effective in obtunding hemodynamic response to pneumoperitoneum, whereas Vidhya et al found the same dose less effective. 18,19 In our study, we found that heart rate did not increase at the time of creation of pneumoperitoneum or at any subsequent time points in both the groups. This may be attributed to the use of a balanced technique of anaesthesia for all the patients.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…[14][15][16] In study by Rekhi et al they found nalbuphine (0.2mg/kg) effective in obtunding hemodynamic response to pneumoperitoneum, whereas Vidhya et al found the same dose less effective. 18,19 In our study, we found that heart rate did not increase at the time of creation of pneumoperitoneum or at any subsequent time points in both the groups. This may be attributed to the use of a balanced technique of anaesthesia for all the patients.…”
Section: Discussionsupporting
confidence: 41%
“…However, the results were found to be contradictory. 18,19 This study was planned to find out the haemodynamic effects of 0.3 mg/kg nalbuphine administered before creation of pneumoperitoneum in patients undergoing laparoscopic surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…In a study done by Balwinder Kaur Rekhi et al, it was found that intravenous dexmedetomidine prolonged the effect of ropivacaine (3 mg). [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…Catecholamines evoke changes in carbohydrate metabolism reflected as an increase in blood sugar levels. 2,10,13 Various drugs have been used to attenuate the stress response in laparoscopic cholecystectomy. Earlier studies have been done with Dexmedetomidine on blood sugar levels compared with fentanyl.…”
Section: Discussionmentioning
confidence: 99%
“…The hemodynamic changes are characterized by increased systemic and pulmonary vascular resistance, a rise in arterial pressure and heart rate with reduced cardiac output. 1,2 Though better tolerated in ASA I and II patients, these changes can be detrimental in elderly and ASA III patients with compromised cardiovascular physiology. 3,4 Various surgical methods and pharmacological agents were used to decrease the surgical stress of laparoscopic procedures to improve outcome.…”
Section: Introductionmentioning
confidence: 99%